Draga Jovanović, Martyrs and Sinners (1937) – A Collection of Short Stories on WWI (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
In the historical, social, political, and artistic documents from WWI, the nameless character of a woman looms over the horrific events, suffering, disease and death like a shadow. In order to define Her contours and reconstruct Her story I have studied the work of women artists who inscribed the experience of the Great War into the literary level. The central place of this women’s archive was given to Draga Jovanović’s short story collection Martyrs and Sinners. Draga Jovanović (1885-1975) was a Serbian writer who graduated from the University of Geneva in 1911. There she won the first prize for the psychodramatic poem “A Night in Venice” (1909). In the first half of the 20th century Jovanović published two novels, No name (1931) and The Case of Vera (1963), two short stories collections Martyrs and Sinners (1937) and Mosaic of Reality and Dreams (1965), a short story “Mother” (1961), a collection of poems Midsummer Night’s Dream (1933) and a play “Autumn Night – Winter Night” (1966). In her works she addressed the problem of motherhood, illegitimate pregnancy in a traditional society, love, disease, and death. In the short story collection Martyrs and Sinners, the once popular and now forgotten writer Draga Jovanović set the framework for describing the female war space in Serbia in 1915, shedding light on life from diferent angles of martyrs and sinners, faced with the horrors of poverty, slavery, famine, and death. The analysis will show that we are faced with a precious artistic testimony of the female side of war, rich in aesthetic value and worthy of entering the literary canon.
Keywords: World War I; war prose; Draga Jovanovic; a collection of stories Martyrs and sinners; women's role in the war